PENDEKATAN YURIDIS TERHADAP PRIVATISASI BADAN USAHA MILIK NEGARA (BUMN) RUMAH SAKIT - Endang Sutrisno (Fakultas Hukum Universitas Swadaya Gunung Jati, 2011)
JURIDICAL APPROACH TO PRIVATIZATION OF STATE-OWNED ENTERPRISES (BUMN) HOSPITAL Development of society in the global era has impacted in all sides of lives, the world's borderless position puts the legal workings of the process activities through time and space. The existence of law referring to the destination is not only purely based on fairness and certainty but also to its utility. For what the law exists, must heed the achievement of the goal even if the three objectives are often positioned on the condition of an argument, which should take precedence.Legal dimensions of corporate economic activity holds the main control, it will be very urgent if the issue of privatization of State Owned Enterprises (BUMN) is become the study because it can result in view of the pros and cons in the community. Certain perceptions emerge the notion that privatization of (BUMN) as a-national behavior by selling the sovereignty of the State which is fitting to build community and alignments in the interest of the people. And considering existence and purpose of establishment of state enterprises under the State Constitution 45 must be able to reflect the needs of all levels of society to build society welfare. Law is the primary guardian in order to achieve privatization goals so that economic activities are not out of control, especially considering global economic development that carries shades of liberalization and global capitalism, profit is more prominent than the public interest. Especially considering the existence of a hospital that carries the value of humanity as a consideration that must remain in the realm of regulation that aims for the goodness of the wider community, including privatization efforts will not escape from it. Key Word : Privatization, Law Objectives, Community Development